1969
DOI: 10.1149/1.2412047
|View full text |Cite
|
Sign up to set email alerts
|

The Electrochemical Behavior of Zinc in Alkaline Media

Abstract: The electrochemical behavior of horizontally disposed planar zinc in 30% (6.9M) potassium hydroxide, alone and saturated with zinc oxide at 25°C, has been investigated in a controlled manner, using both galvanostatic and potentiostatic techniques. The anodic characteristics have been interpreted in terms of a kinetically controlled process preceding a diffusion step. The cathodic behavior of oxidized zinc has been interpreted in terms of a complex two‐state process, involving the formation of a bound zinc hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

1970
1970
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“…Potential-time curve.--Our potential vs. time curves were similar to those observed by Dirkse and Hampson (13), except that we observed a short-life transition just prior to the onset of passivation, as also observed by Bartelt and Landsberg (7) and Elder (12). Since the electrode potential at the transition is in the vicinity of the Zn/ZnO standard potential, the transition may be associated with the direct formation of the passivating type II ZnO film observed by Powers and Breiter (15).…”
Section: Discussionsupporting
confidence: 88%
“…Potential-time curve.--Our potential vs. time curves were similar to those observed by Dirkse and Hampson (13), except that we observed a short-life transition just prior to the onset of passivation, as also observed by Bartelt and Landsberg (7) and Elder (12). Since the electrode potential at the transition is in the vicinity of the Zn/ZnO standard potential, the transition may be associated with the direct formation of the passivating type II ZnO film observed by Powers and Breiter (15).…”
Section: Discussionsupporting
confidence: 88%
“…In stirred solution the current initially rose fairly rapidly to the same potential at which the peak was observed in the unstirred case and from there continued to rise until passivation occurred but with a greatly reduced slope. Elder (12), who also studied the dissolution of zinc in unstirred 7M KOH solution, found that at a scan rate of 2.8 mV.sec -1 the current passed through a small peak at --1.12V and then commenced to rise again just before the onset of passivation. The peak potential and current were found to obey the relationship Ep = --0.701 + 0.5246 log ip for scan rates within the range 0.56-139.0 mV.sec -1.…”
mentioning
confidence: 99%
“…Other studies claim that the rate determining step could be also diffusion of zincate species from the surface of the electrode [25,28,124] . As demonstrated below in Figure 9(a), there is a certain initiation step, denoted as t a in the scheme, at which the produced zincate ions accumulate over time due to a slow dissipation diffusion rate.…”
Section: Anode Related Challengesmentioning
confidence: 95%
“…Other studies claim that the rate determining step could be also diffusion of zincate species from the surface of the electrode. [25,28,124] As demonstrated below in Figure 9(a), there is a certain initiation step, denoted as t a in the scheme, at which the produced zincate ions accumulate over time due to a slow Figure 9. (a) Proposed scheme for the processes associated with the anodic passivation of zinc in alkaline solutions, t -total time to passivation (t = t a + t b + t c ), t a -anodic reaction proceed up to this time, zincate accumulates in the vicinity of the electrode and its concentration reaches to a critical one at which the type I ZnO begins to precipitate, t b -mass transport rate of hydroxide ions through type I layer permits the continuation of electrode reaction up to falling below the required for the zincate formation reaction -type II ZnO formation initiated on the electrode surface, t c -limited mass transport of hydroxide ions is reached -the surface is fully covered with type II ZnO layer.…”
Section: Passivation Phenomenonmentioning
confidence: 99%